ZXY International FZCO: Merchandising & Marketing, Supply Chain, Sample & Development, Quality Management, HRM & CSR - Sarkar, Nabo Kumar (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2021.